Feeding the inner critic: Self-Criticism and Shame in the association of Affiliative Memories with Emotional and Disordered Eating in women - Azevedo, Ana Rita Latães (2024)
Dissertação de Mestrado em Intervenções Cognitivo-Comportamentais em Psicologia Clínica e da Saúde apresentada à Faculdade de Psicologia e de Ciências da Educação